Управлінські аспекти інноваційної діяльності підприємств виробників молочної продукції - Халін, Станіслав Васильович; Чуб, Олег Анатолійович (Національний технічний університет "Харківський політехнічний інститут", 2025)
Стаття присвячена дослідженню управлінських аспектів інноваційної діяльності підприємств виробників молочної продукції задля напрацювання рекомендацій щодо вдосконалення їхнього інноваційного розвитку. Визначено, що інноваційна діяльність у сучасних умовах є не просто впровадженням окремих технологічних нововведень, а комплексним процесом, що інтегрує всі функціональні напрями діяльності підприємства з метою забезпечення довгострокової ефективності, адаптивності та стійкості до викликів ринку. Доведено, що ефективне управління цією діяльністю вимагає всебічного підходу, що включає як технологічні інновації, так і вдосконалення організаційних та управлінських механізмів. Встановлено, що сучасні управлінські підходи орієнтовані на формування гнучкої системи прийняття рішень, здатної оперативно адаптуватися до змін у ринковому середовищі. Узагальнено, що управління інноваційними процесами в молочній галузі має ґрунтуватися на системності, орієнтації на сталість розвитку, дотриманні високих стандартів якості та здатності до оперативного реагування на зміну споживчих потреб.

The article is devoted to the study of the management aspects of the innovative activity of dairy enterprises to develop recommendations for improving their innovative development. It is determined that innovative activity in the dairy industry today is not only an important condition for ensuring competitive advantages, but also a determining factor in the strategic growth of enterprises. Effective management of this activity requires a comprehensive approach, including both technological innovations and the improvement of organizational and management mechanisms. It is established that modern management approaches are focused on the formation of a flexible decision making system capable of quickly adapting to changes in the market environment. This involves the optimization of internal innovation management processes, the development of human resources, the digital transformation of production and logistics processes, as well as the active formation of partnerships with scientific institutions, suppliers, and other participants in the innovation ecosystem. It is proven that rational financial support for innovative activity is no less important. To achieve this, enterprises should utilize various financing sources (both external and internal) while implementing mechanisms to optimize costs and enhance energy efficiency. The management of innovation processes in the dairy industry should be based on systematicity, orientation towards sustainable development, adherence to high quality standards, and the ability to respond promptly to changing consumer needs. Only under such conditions is stable growth possible, strengthening market positions and realizing new development opportunities.
Management aspects of innovative activities of dairy production enterprises
Keywords: економічна ефективність; інноваційна діяльність; інноваційні рішення; конкурентоспроможність; підприємства виробники молочної продукції; сталий розвиток; управління; economic efficiency; innovative activity; innovative solutions; competitiveness; dairy enterprises; sustainable development; management